STUDY OF THE AERODYNAMICS OF THE FLOW OF THE COMBUSTION CHAMBER OF A POWER PLANT WITH VARIOUS SUPPLY OF SOLID FUEL - Safarik, P.; Askarova, A.S.; Bolegenova, S.A.; Maksimov, V.Yu.; Bolegenova, S.A.; Ospanova, Sh.S.; Nugymanova, A.O. (Recent Contributions to Physics, 2022)
Numerical modeling methods have been used to study the effect of an emergency stop of the fuel mixture supply through individual burners on the aerodynamics of the flow in the combustion chamber of a power boiler. The performed computational experiments made it possible to obtain the main aerodynamic characteristics of heat and mass transfer processes (full velocity vector, pressure, kinetic energy of turbulence and dissipation energy) in the volume of the combustion chamber and at the exit from it in emergency mode (two swirl burners are operating) and compare them with traditional solid fuel combustion (basic mode - four direct-flow burners are working). The results obtained indicate that with a vortex fuel supply in the central region of the combustion chamber, a sharp change in aerodynamic characteristics is observed with the formation of a vortex flow, which weakens as the pulverized coal flow and combustion products move to the exit. The presence of a vortex flow causes stable combustion of solid fuel and uniform distribution of heat flows along the walls of the combustion chamber. In addition, the vortex nature of the flow increases the residence time of coal particles in the combustion chamber, which contributes to a more complete burnout and a decrease in the mechanical underburning of the fuel mixture. Such a detailed study of the aerodynamic flow pattern that takes place in the combustion chamber of power boilers of operating TPPs can only be obtained by numerical simulation methods and by performing computational experiments. The highly informative results obtained make it possible to develop “clean” energy production technologies and solve environmental problems of the emission of harmful substances into the environment.